Management of Tourist Objects to Increase Tourist Visits to the Situ Wangi Tourism Area, Winduraja Village, Kawali District, Ciamis Regency - Fika Febriani; Neti Sunarti; Arie Budiawan (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
This research is motivated by the suboptimal management of the Situ Wangi tourist attraction in Winduraja Village, Kawali District, Ciamis Regency, in increasing tourist visits. This study aims to determine how tourist attraction management increases tourist visits to the Situ Wangi tourist attraction in Winduraja Village, Kawali District, Ciamis Regency. This study used a qualitative descriptive research method. Data collection techniques were conducted through observation, interviews, and documentation. Informants in this study consisted of the Tourism Office, Tourism Technical Implementation Unit (UPTD), tourism managers, village government, the community, and tourists. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. This study uses George R. Terry's management function theory, which includes planning, organizing, actuating, and controlling. The results show that the management of the Situ Wangi tourist attraction has been implemented through the functions of planning, organizing, implementing, and monitoring, but its implementation has not been fully optimized. In terms of planning, the management has developed a tourism development program, but there are still limitations in the development of facilities and promotional strategies. In terms of organization, cooperation between relevant parties has been established, but coordination and collaboration still need to be improved. In terms of implementation, tourism promotion through digital media has not been optimal, and some supporting tourism facilities remain inadequate. In terms of supervision, monitoring has been carried out by the management, but increased oversight of tourism facilities and services is still needed. Therefore, increased cooperation between managers, strengthening digital promotion, and improving facilities and infrastructure are needed to optimize Situ Wangi tourism management and increase tourist visits.Keywords: Management, Tourist Attraction, Tourism, Tourist Visits.